Evaluative reasoning in complexity - King, Julian (Evaluation and Value for Investment, 2023)

The Collaborative, Participatory & Empowerment Evaluation Topical Interest Group - American Evaluation Association
designed to foster collaboration, share knowledge, and promote scholarship, this TIG is a division of the American Evaluation Association (AEA).

Participatory Evaluation - Better Evaluation (Better Wvaluation)
Participatory evaluation is an approach that involves the stakeholders of a programme or policy in the evaluation process. This involvement can occur at any stage of the evaluation process, from the evaluation design to the data collection and analysis and the reporting of the study. A participatory approach can be taken with any impact evaluation design, and with quantitative and qualitative data. However, the type and level of stakeholder involvement will necessarily vary between different types, for example between a local level impact evaluation and an evaluation of policy changes (Gujit 2014, p.1). It is important to consider the purpose of involving stakeholders, and which stakeholders should be involved how, in order to maximise the effectiveness of the approach.